Investigation of the Effects of Freeze-Thaw Cycles on Geomechanical and Acoustic Characteristics of Tuff Specimens under Different Stress Paths - Yong-gang Xiao; Chang-hong Li; Jie Cao; Yu Wang; Zhi-qiang Hou; Nan Hu (Advances in Civil Engineering)
In the process of development and construction of open-pit mine slope in the high altitude and cold area, freeze-thaw (F-T) cycles have an important impact on rock engineering structure. F-T cycles lead to the decrease in physical and mechanical properties of rock, which is closely related to the stability of open-pit slope. In this paper, the influence of F-T cycles on geomechanical and acoustic emission (AE) characteristics of tuff specimens under different stress paths was studied by using F-T cycle treatment, in situ AE monitoring, and uniaxial loading test. The results indicated that under the same stress path, the cumulative AE count/energy of rock samples subjected to F-T cycles was less than that of rock samples not subjected to F-T cycles. The peak frequency distribution of AE signal during the loading process of rock specimen presented the phenomenon of frequency bands. The width of the low-frequency band of the rock samples subjected to F-T cycles was larger than that of the rock samples under the natural state. The frequency and width of the high-frequency band of the rock samples subjected to F-T cycles were larger than those of the rock samples under the natural state. The rock samples subjected to F-T cycles had higher plastic strain than those without F-T cycles. According to the uniaxial compression test results of F-T rock samples under different stress paths, the peak stress and peak strain have little change, but the AE characteristics were obviously different.